Estresse em motoristas de transporte coletivo urbano por ônibus - Tavares, Flávia de Andrade (2010)
The stress at work has been too investigated in Brazil and abroad due to their harmful consequences to individuals and organizations. The profession of driver has already been identified as one of the most subject to the occurrence of stress. In view of these issues, the present study aimed to know which factors bus drivers consider as stressors at work, and also identify wheather they are under stress, and which are the symptoms and the stress phase they present. A sample with 134 drivers from two public transportation companies in Uberlandia, Minas Gerais, participated in this study, using as instrument an interview script composed by questions related to the perceived stress factors, to personal and professional data and the Lipp Inventory of Stress for Adults - ISSL. All data obtained have been entered into a spreadsheet SPSS for Windows program, version 17.0, for performing statistical analysis. The answers obtained with the interviews were subjected to content analysis, getting seven categories of stressors, among them "traffic", "social relationships" and "pressure of time" were predominant. Personal and professional data were correlated with data about stress using statistical analysis through Pearson correlation and Chi-square. The analysis by the Pearson coefficient showed that the greater the time in the current company, more symptoms of stress were reported. The associations obtained with Chi-square only were significantly to those who responded positively to the questions "Are you experiencing a problem outside the work situation that is causing your stress?" and/or "Have you ever had any health problem due to your work?" Further the subjects that have pointed the categories Low power" and "Social relationships" represented a proportional greater stress than those who haven t. The index of stress presented by the sample was 34,3%, and that was considered comparatively low. Among the drivers who have stress, the resistance phase and the psychological symptoms were predominant. It is suggested that future research investigate the specific working conditions of Uberlândia and the public transportation companies of the city.